The role of short supply chains and local food systems in the concept of food sovereignty and food democracy - Kapała, Anna (Przegląd Prawa Rolnego, 2023)
The article discusses the role that short supply chains (SSCs) and local food systems (LFS) play in the implementation of food sovereignty and food democracy. The question asked is whether it is justified to seek alternatives to global and industrial food systems, bearing in mind, on the one hand, their negative effects and, on the other hand, food challenges as well as the objectives and assumptions of the EU policy expressed in the “Farm to Fork” strategy. The conducted analysis has shown that SSCs and LFS play a key role in food sovereignty and food democracy, as they contribute to building sustainable and equitable food systems that provide nations with control over the way they produce, and control of the food self-sufficiency and sovereignty over food supply, social bonds, choice of alternatives to industrial products, as well as information on food and its origin.